Drying and Extraction Methods Effect on Biochemical and An-tioxidant Capacity of Malaysian Wild Edible Vegetables - Mat Rashid, Zalilawati; Aziz, Natasha; Mat, Nashriyah (International Journal of Engineering and Technology, 2018)
Some wild edible vegetables are rarely been studied albeit freshly consumed by local people as â€˜ulamâ€™. Due to their perishable nature, drying is applied to extend their shelf life which causes substantial changes in phytochemicals content. Hence for collection of optimum yield of phenolics, the use of solvents of different polarities is crucial. In this study, the effect of drying (freeze-drying and oven-drying) and extractants solvents (ethanol and water) methods on phenolics and flavonoids contents as well as antioxidant activity of ten immature wild edible vegetables extracts (Acrosticum aureum, Erechtites hieraciifolia, Erechtites valerianifolia, Gnetum gnemon, Manihot esculenta, Oroxylum indicum, Phyllanthus acidus, Piper sarmentosum, Terminalia catappa and Ziziphus mauritiana) collected in Terengganu, Malaysia were investigated. Extraction were carried out using ultrasonication-assisted method. The results indicated that some vegetables were good sources of antioxidants with the lowest IC50 value of DPPH scavenging was 6.19 Î¼g/mL. Ethanolic freeze dried (EFD) extracts (0.5 mg/mL) showed stronger DPPH scavenging activity (Inhibition rates: 76 to 88%) compared to ethanolic oven dried (EOD) (56 to 88%) and aqueous freeze dried (AFD) (35 to 89%). Total phenolics content (TPC) and total flavonoid contents (TFC) were found to exhibit strong to moderate correlations with antiradical power. Among all samples, T. catappa following EFD, EOD and AFD showed the strongest antioxidant potential. The findings revealed that different drying methods and extracting solvents did influence the biochemicals isolation and antioxidant activity.Â Â Â